2002
DOI: 10.1152/ajpgi.00088.2002
|View full text |Cite
|
Sign up to set email alerts
|

I. Shiga toxin B-subunit system: retrograde transport, intracellular vectorization, and more

Abstract: Many intracellular transport routes are still little explored. This is particularly true for retrograde transport between the plasma membrane and the endoplasmic reticulum. Shiga toxin B subunit has become a powerful tool to study this pathway, and recent advances on the molecular mechanisms of transport in the retrograde route and on its physiological function(s) are summarized. Furthermore, it is discussed how the study of retrograde transport of Shiga toxin B subunit allows one to design new methods for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…32,[34][35][36] In our study, the quantitative determination of CD77 revealed notable concentration differences among the individual Fabry patients (2-21%), which may be caused by different a-Gal A levels, due to the great variety of a-Gal A gene mutations. In contrast to the assumption 37 that the plasma Gb3 levels reflect the Gb3 tissue load, Young 38 recently showed that Gb3 in plasma and urine cannot be used as a reliable biomarker for AFD especially in patients with the N215S mutation and many heterozygotes.…”
Section: Cd77 Expression On Cells With A-gal a Deficiencymentioning
confidence: 98%
“…32,[34][35][36] In our study, the quantitative determination of CD77 revealed notable concentration differences among the individual Fabry patients (2-21%), which may be caused by different a-Gal A levels, due to the great variety of a-Gal A gene mutations. In contrast to the assumption 37 that the plasma Gb3 levels reflect the Gb3 tissue load, Young 38 recently showed that Gb3 in plasma and urine cannot be used as a reliable biomarker for AFD especially in patients with the N215S mutation and many heterozygotes.…”
Section: Cd77 Expression On Cells With A-gal a Deficiencymentioning
confidence: 98%
“…However, a clathrin-independent mechanism mediated by lipid rafts has also been described (Johannes, 2002). The carbohydrate part, and also the fatty acid part, of Gb3 are important for toxin binding (Binnington et al, 2002).…”
Section: Intracellular Trafficking Of St and Related Toxinsmentioning
confidence: 99%
“…To substantiate the specificity and topology of this block, we analyzed the retrograde transport routes as well. Transport kinetics of STB, known to employ a Rab6‐dependent but COPI‐independent pathway (62, 63), remained unaltered by EBAG9 expression (Fig. 11).…”
Section: Resultsmentioning
confidence: 99%